2016
DOI: 10.1111/jora.12263
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Racial Discrimination, Cultural Mistrust, and Gender in Latina/o Youth's School Attitudes and Academic Achievement

Abstract: Gender gaps in achievement are particularly pronounced among Latina/os, who are among the population most affected by the academic achievement gap. This study examined the roles of racial discrimination, cultural mistrust, and economic value of education in the academic achievement of urban, low-income Latina/o adolescents. Participants were 346 high school students. Structural equation modeling revealed that the model of associations was a better fit for male students than for female students. Cultural mistru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…The Roma ethnic-cultural group is one of the groups that suffers more discrimination and social exclusion in Europe. Suffering ethnic-cultural discrimination at school causes feelings of disengagement from the school as well as low expectations about what they can contribute (Cooper and Sánchez, 2016). Ethnic-cultural bullying could be a very adverse factor for programs and policies of educational and social inclusion whose purpose is assisting the Roma population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Roma ethnic-cultural group is one of the groups that suffers more discrimination and social exclusion in Europe. Suffering ethnic-cultural discrimination at school causes feelings of disengagement from the school as well as low expectations about what they can contribute (Cooper and Sánchez, 2016). Ethnic-cultural bullying could be a very adverse factor for programs and policies of educational and social inclusion whose purpose is assisting the Roma population.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic-cultural bullying could be a very adverse factor for programs and policies of educational and social inclusion whose purpose is assisting the Roma population. Taking into consideration the negative effects of ethnic-cultural discrimination and violence among minors (e.g., Garnett et al, 2014; Priest et al, 2014; Baysu et al, 2016; Cooper and Sánchez, 2016; Brüggemann and D’Arcy, 2017; Gkofa, 2017), it is essential to continue studying ethnic-cultural bullying. The scientific knowledge of this phenomenon will provide a better protection of the minors’ physical and psychological integrity in pluricultural contexts and the development of educational policies and strategies that are effective to prevent and eradicate discrimination, racism and xenophobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, other variables could have been taken into account. Previous studies have shown that other environmental factors may influence students’ academic and emotional functioning, such as the quality of relationships with parents or parental styles (Buehler, Benson, & Gerard, ) as well as cultural and socioeconomic variables (Cooper & Sánchez, ; Ponnet, Van Leeuwen, Wouters, & Mortelmans, ). Similarly, individual characteristics such as temperament variables (Helzer, Connor‐Smith, & Reed, ), trait emotional intelligence (Mavroveli, Petrides, Sangareau, & Furnham, ), and motivational factors are important for psychological and academic functioning and may be analyzed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would have been difficult to obtain significant predictions of ethnic pride given girls’ lower variability. Ethnic pride may have been more variable for Mexican-origin males than females because young men of color likely experience harsher social conditions intertwined with their identities and perceived school roles (Cooper & Sánchez, 2016; Sáenz & Ponjuan, 2011). Especially important, however, the findings suggest that ethnic pride may promote a sense of belonging in school for both Mexican-origin boys and girls.…”
Section: Discussionmentioning
confidence: 99%